Duality and Complexity of Allergic Type Inflammatory Mechanisms in Determining the Outcome of Malaria Disease - Blank, Ulrich; Mécheri, Salaheddine (Frontiers in Immunology, 2011)
One of the effector arms of the pathogenesis of severe forms of malaria disease is the development of uncontrolled or excessive inflammatory response. A characteristic inflammatory response may arise from the propensity of some individuals to produce IgE antibodies against environmental antigens or against parasite components. We believe that an allergic inflammatory response which develops concomitantly with a malaria episode may drive the disease course towards severe forms. The role of IgE-FcεRI complex in malaria severity in Plasmodium falciparum-hosting patients is unknown. Subsequently, except a very limited number of reports, study of effector cells that express this complex such as mast cells and basophils and that may contribute to malaria pathogenesis have been particularly neglected. A better understanding of this type of inflammatory response and its implication in malaria disease and how it impacts Plasmodium parasite development may provide additional tools to alleviate or to cure this deadly disease.